ANALISIS KAUSALITAS DAN KOINTEGRASI ANTARA TINGKAT SUKU BUNGA BANK INDONESIA (BI RATE) DENGAN SUKU BUNGA BANK AMERIKA SERIKAT (THE FED) - Lasma Melinda Siahaan; Paidi Hidayat (Ekonomi dan Keuangan, 2013)
This study aims to analyze Causality and Cointegration among Interest Rates of Bank Indonesia (BI Rate) and the U.S. Interest Rate (the Fed), using time series data, that is a monthly data during the time period January 2008 to November 2013. The method used to test the causality is Granger's Causality method, and the method used to test cointegration is Johansen's Multivariate Cointegration Test. The results of the analysis data shows that there is a cointegration between the Interest Rate of Bank Indonesia (BI Rate) and U.S. Interest Rate (the Fed). It means that between the Interest Rate of Bank Indonesia (BI Rate) and U.S. Interest Rate (the Fed) have a long-term equilibrium relationship. While the results of the Granger Causality test found a direct relationship. It means that only variable of U.S. Interest Rate (the Fed) affects the Interest Rate of Bank Indonesia (BI Rate), while the Interest Rate of Bank Indonesia (BI Rate) does not affect the U.S. Interest Rate (the Fed).Keywords : BI Rate, the Fed, Granger’s Causality, Johansen’s Multivariate Cointegration Test.